Living standards and inequality in the Industrial Revolution: Evidence from the height of University of Edinburgh students in the 1830s - Matthias Blum; Eoin McLaughlin (Queen's University Centre for Economic History (QUCEH), 2019)
Trends in living standards during the Industrial Revolution is a core debate in economic history. Studies using anthropometric records from institutional sources have found downward trends in living standards during the first half of the nineteenth century. This paper contributes to this literature by utilising an overlooked source of middle and upper class anthropometric data: the height and weight of university students. Combined with more traditional anthropometric sources these data give us a snapshot into the range of living standards experienced by different sections of society in the United Kingdom. Our findings suggest that inequality was most pronounced in Ireland, followed by England. Height inequality in Scotland was still substantial, but somewhat lower in comparison.
Keywords: D63; I14; N13; 330; height; anthropometrics; Industrial Revolution; economic history; United Kingdom